PEAK leadership. Issue 67 (14th December 2012) - Conley, Chip
Abstract: Conley asks why business leaders don't think of themselves as engaging in a practice, as in medicine or law. Based on the hierarchy of needs and theory of peak potential of psychologist Abraham Maslow, Conley describes seven practices for organizations to reach the highest levels. These include taking a positive view of human nature, cultivating the ability to move between transactional and transformational leadership, and focusing on your customers' highest needs. "If you create a unique corporate culture, " he writes, "it tends to drive employee happiness that enhances customer loyalty that grows market share and leads to sustained profitability."